Diurnal temporal patterns of hypoglycaemia in hospitalized people with diabetes may reveal potentially correctable factors. Issue 12 (29th June 2013) - Kerry, C.; Mitchell, S.; Sharma, S.; Scott, A.; Rayman, G.
Abstract Aim To determine whether diurnal temporal variations in hypoglycaemic frequency occur in hospitalized patients. Methods Hypoglycaemic events were identified in a snapshot bedside audit of capillary blood glucose results from diabetes charts of all inpatients receiving insulin or a sulphonylurea (with or without insulin) on 2 days separated by 6 weeks. Additionally, capillary blood glucose measurements were remotely captured over 2 months, in the same category of patients, and analysed for temporal patterns. Hypoglycaemia was defined as 'severe' when the capillary blood glucose was < 3.0 mmol/l and 'mild' when the capillary blood glucose was between 3.0 and 3.9 mmol/l. Results The bedside audit found that 74% of those audited experienced a hypoglycaemia event. Eighty‐three per cent of all hypoglycaemic events and 70% of severe events were recorded between 21.00 and 09.00 h. This was confirmed in the longer duration remote monitoring study where 70% of all hypoglycaemic events and 66% of severe events occurred between 21.00 and 09.00 h. Conclusion Hypoglycaemia occurs more frequently between 21.00 and 09.00 h in hospitalized patients receiving treatments that can cause hypoglycaemia. This may be related to insufficient carbohydrate intake during this period, and is potentially preventable by changes in catering practice.